Endoscopic sphincterotomy to prevent post-ERCP pancreatitis in patients with biliary neoplasms: a multicenter retrospective cohort study - Tamura, Takashi; Ogura, Takeshi; Takenaka, Mamoru; Tanioka, Kensuke; Itonaga, Masahiro; Yamao, Kentaro; Kamata, Ken; Hirono, Seiko; Okada, Ken-ichi; Imanishi, Miyuki; Higuchi, Kazuhide; Yamaue, Hiroki; Kitano, Masayuki (Endoscopy International Open, 2020)
Background and aims Treatment of biliary neoplasms often involves multiple endoscopic retrograde cholangiopancreatography (ERCP)-related procedures. Endoscopic sphincterotomy (ES) may prevent post-ERCP pancreatitis (PEP). This retrospective, multicenter cohort study aimed to investigate the effectiveness of ES for prevention of PEP in patients with biliary neoplasm.Methods Patients with biliary duct neoplasm who underwent ERCP between January 2006 and December 2016 were enrolled. The frequency of PEP was compared between the ES and non-ES groups using propensity score analysis. The effectiveness of ES in subgroups of patients who underwent biliary duct stent placement, intraductal ultrasound (IDUS), and transpapillary biliary duct biopsy was analyzed by logistic regression.Results Of the 362 patients enrolled, 84 (23.2 %) developed PEP. Propensity score matching for PEP risk factors in 172 ERCP procedures showed that the frequency of PEP in the ES group was lower than that in the non-ES group (19.7 % vs. 33.7 %). Non-ES was also an independent risk factor for PEP in patients who underwent intraductal ultrasound and transpapillary biliary duct biopsy (RR = 4.54 and 5.26), but was not an independent risk factor for PEP in patients with biliary duct stents. In addition, there was no evidence that the frequency of PEP was statistically different between patients with plastic stents and metal stents in the ES and non-ES groups (P = 0.14 and 0.10).Conclusions ES is an effective technique to prevent PEP in patients with biliary neoplasms. In particular, ES is a safe technique to prevent PEP when performing IDUS and transpapillary biliary duct biopsy.